Movements of beluga whales (Delphinapterus leucas) in Bristol Bay, Alaska. Issue 4 (25th July 2016) - Citta, John J.; Quakenbush, Lori T.; Frost, Kathryn J.; Lowry, Lloyd; Hobbs, Roderick C.; Aderman, Helen
Abstract: We describe the annual distribution of beluga whales ( Delphinapterus leucas ) in Bristol Bay, Alaska, using data from 31 satellite‐linked transmitters during 2002–2011. Bristol Bay has one of the largest and best studied Pacific salmon ( Oncorhynchus spp.) fisheries in the world, allowing us to link the seasonal distribution of belugas to that of salmon. During salmon migrations, beluga movements were restricted to river entrances. Belugas generally did not relocate to different river entrances or change bays during peak salmon periods. However, the location of belugas was not related to the number of salmon passing counting towers, suggesting that belugas were either selecting locations that were good for catching salmon or there were simply more salmon than belugas needed to supply their nutritional needs. The distribution of belugas expanded after salmon runs ended, and was greatest in winter when belugas ranged beyond the inner bays, traveling as far west as Cape Constantine. Belugas continued to frequent the inner bays in winter whenever sea ice conditions allowed, e.g ., when winds moved sea ice offshore; however, they were never located south of the southern ice edge in open water or outside of Bristol Bay.